The political economy of reciprocity. A reply - H.W. ARNDT (PSL Quarterly Review, 2013)
The need for reciprocity clauses in tariff reductions should not distort the real picture concerning international trade. Although reciprocity clauses can help countries which follow more expansionary macroeconomic policies than their trade partners, they can never be the perfect panacea for unemployment problems. Reciprocity clauses only encourage protectionist trade practices.